“Analisis Pengaruh Faktor Budaya terhadap prilaku keputusan Pembelian Konsumen dalam bisnis Internasional” - Muhammad Yuda Hendrawan; Hendra Ibrahim (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The development of the world of international business creates a new dynamic regarding consumer behavior where consumers have personality traits that may be inherent due to existing culture or originate from inner turmoil to make changes related to meeting needs. Consumers' product purchasing decisions can be influenced by cultural factors in various countries. The existence of different societal needs and environmental conditions which include various things, such as lifestyle, economics, social, political and cultural, also encourage and influence consumer purchases. Kotler (2008) says that culture is the most basic cause of a person's desires and behavior, a person's behavior is learned and grows in a society or country, as a person learns the basic values of perception, desires and behavior from family and institutions. -important institutions in other countries. Literature study methodology was used to conduct this research. Cultural factors can influence purchasing behavior in a variety of ways, including product or service presentation, marketing communications, and how a company interacts with customers.